STUDENT INTEREST IN CONTINUING THEIR STUDIES TO HIGHER EDUCATION - Putri, Nanda Eka; Mardi; Pratama, Aditya (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
This study aims to analyze the factors that influence the interest in continuing their studies to higher education.. The population of this research is high school students of class XII in the academic year 2021/2022. The number of samples used amounted to 268 students with simple random sampling technique. This study uses a quantitative technique with a Path Analysis approach. In this study there were 5 hypothesis tests with the results showing 4 accepted and 1 rejected. The results showed that the peer environment had a positive and significant effect on the interest in continuing their studies to higher education, the socioeconomic status of parents had a negative and significant effect on the interest in continuing their studies in higher education, learning motivation had a positive and significant effect on the interest in continuing their studies in higher education, the peer environment have an indirect effect on the interest in continuing their studies to higher education through significant learning motivation, the socioeconomic status of parents has an indirect effect on the interest in continuing their studies to higher education through significant learning motivation. Based on these results, it can be concluded that choosing friends is very important, because peers have a big impact on changes in student behavior and psychology. And the low socioeconomic status of parents does not discourage students from continuing their studies to higher education. Researchers suggest that every school from the start of students being accepted has directed students' interest to continue their studies.